Atomically Dispersed Copper–Platinum Dual Sites Alloyed with Palladium Nanorings Catalyze the Hydrogen Evolution Reaction. (15th November 2017) - Chao, Tingting; Luo, Xuan; Chen, Wenxing; Jiang, Bin; Ge, Jingjie; Lin, Yue; Wu, Geng; Wang, Xiaoqian; Hu, Yanmin; Zhuang, Zhongbin; Wu, Yuen; Hong, Xun; et al.
Abstract: Designing highly active catalysts at an atomic scale is required to drive the hydrogen evolution reaction (HER). Copper–platinum (Cu‐Pt) dual sites were alloyed with palladium nanorings (Pd NRs) containing 1.5 atom % Pt, using atomically dispersed Cu on ultrathin Pd NRs as seeds. The ultrafine structure of atomically dispersed Cu‐Pt dual sites was confirmed with X‐ray absorption fine structure (XAFS) measurements. The Pd/Cu‐Pt NRs exhibit excellent HER properties in acidic solution with an overpotential of only 22.8 mV at a current density of 10 mA cm −2 and a high mass current density of 3002 A g −1 (Pd+Pt) at a −0.05 V potential.